Increasing cropping options in seasonal floodplain wetlands of Sub-Saharan Africa: a remote-sensing approach for assessing available green water for cultivation [Abstract only] - Ayyad, S.; Karimi, P.; Langensiepen, M.; Ribbe, L.; Rebelo, Lisa-Maria; Becker, M. (Copernicus GmbH, 2022)
Producing more food for a growing population requires sustainable crop intensification and diversification, particularly in high-potential areas such as the seasonal floodplain wetlands of sub-Saharan Africa (SSA). With emerging water shortages and concerns for conserving these multi-functional wetlands, a further expansion of the cropland area must be avoided as it would entail increased use of blue water (surface and groundwater) for irrigation and infringe on valuable protected areas. We thus advocate an efficient use of the prevailing green water (plant-available water stored in the soil) on the existing cropland areas in seasonal floodplain wetlands, where small-scale farmers grow a single crop of rainfed lowland rice during the wet season. However, soil moisture at the onset of the rains (pre-rice niche) and residual soil moisture after rice harvest (post-rice niche) may suffice to cultivate short-cycled crops. We developed a methodological approach to analyze the potential for green water cultivation in the pre- and post-rice niches in the Kilombero Floodplain in Tanzania, as a representative case for seasonal floodplain wetlands in SSA. The three-step approach used open-access remote sensing datasets to: (i) extract cropland areas following a cross-comparison of multiple land cover products; (ii) analyze soil moisture conditions using evaporative stress indices to identify the pre- and post-rice niches (using MOD16A2GF potential (PET) and actual (AET) evapotranspiration products), and (iii) quantify the green water availability in the identified niches (using an ensemble mean of SSEBop and WaPOR to calculate AET).